2013
DOI: 10.1007/s11262-013-1025-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and phylogenetic analysis of an orf virus from sheep in Makhdoom, India

Abstract: Orf (contagious ecthyma) is an exanthematic disease caused by a parapoxvirus and occurs primarily in sheep and goats with zoonotic implications. In the present investigation, an orf outbreak in the Muzzaffarnagari sheep flock at the Central Institute for Research on Goats (CIRG), Makhdoom, Mathura, Uttar Pradesh, India, was investigated. Primary goat testes cell culture was used for isolation of the orf virus (ORFV) for the first time. The identity of the virus was confirmed by amplification and sequence analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 35 publications
3
41
0
1
Order By: Relevance
“…The envelope gene (B2L) of ORFV encodes a highly immunogenic envelope protein of about 42 kDa. The B2L, DNA polymerase, GIF/IL-2 and VIR genes have been used in studies related to genetic variation and molecular epidemiology [3,12,14,15].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The envelope gene (B2L) of ORFV encodes a highly immunogenic envelope protein of about 42 kDa. The B2L, DNA polymerase, GIF/IL-2 and VIR genes have been used in studies related to genetic variation and molecular epidemiology [3,12,14,15].…”
mentioning
confidence: 99%
“…CPDV/IND2013/02 showed 98 % nt identity with a most recent isolate from Central Institute for Research on Goats (CIRG), Makhdoom, Mathura, (Accession no. KC992325) [12]. Although CPDV strains isolated from different hosts grouped very closely in the phylogenetic tree showing very high identity levels, Kumar et al [12] have identified a critical amino acid (aa) residue at position 249 in the B2L gene.…”
mentioning
confidence: 99%
See 3 more Smart Citations